Estudo da incorporação de hidroxiapatita e pentóxido de nióbio nano em resina composta odontológica - Leite, Josélia da Silva (2022)
Restorative composites have evolved significantly since the 1960s, with most development focusing on filler technology. This has led to improved mechanical properties, particularly wear resistance, and has expanded the use of composites for larger posterior tooth restorations. The lack of clinical correlation between the use of these materials and better outcomes has more recently shifted focus to improvements in the materials' resistance to degradation in the oral environment caused by aqueous solvents and salivary enzymes and biofilm formation. Thus, niobium pentoxide (Nb2O5) due to its properties: electrical, thermal and corrosion resistance, can bring improvements to restorative composite materials, when added. On the other hand, Hydroxyapatite (HAp), a mineral present in teeth and bones, is easily obtained and is the most used biomaterial in the medical field. In this particular study, it was used due to a peculiarity already mentioned in the literature, as it is an artificial substrate that causes adhesion, or another favorable biological response, to the host. In this work, dental resins were developed with the aim of filling empty spaces on dental surfaces (restorations), as they undergo the process of polymerization contraction over time, causing relapse of caries, fracture and total displacement of the material from the dental cavity. Bringing to this restorative material a greater capacity to resist for a longer period of time in the oral cavity. Restoration retention can be obtained by combining chemical, mechanical and micromechanical mechanisms, which are directly related to the type of matrix reinforcement. Composite resins have in their constitution the organic matrix that is responsible for strength, rigidity and stability. The inorganic filler in which it confers rigidity in the most superficial portion and improves the resistance to compression and traction, increasing its durability. This research made use of Nb2O5 nano powder, in proportions of 0.02g and 0.01g, following the experiments carried out in other studies cited in the literature, and Hydroxyapatite in proportions of 0.02g and 0.04g. Proportions also already mentioned in previous studies as reinforcing materials. The minerals were added to a commercial nanohybrid photopolymerizable composite resin. As an exclusion criterion, constituent resins with inorganic reinforcements ( Zirconia). Resins with these reinforcements have already been scientifically proven to be more hard and long. The samples were constructed using the experimental design in order to reduce possible segments in which each variable was analyzed. Where responses were obtained for each constituent of the study. For the samples of the constructed resins, pH, solubility, profilometry, colorimetry and microhardness analysis were performed. Starting materials were also characterized by X-ray diffraction; scanning electron microscopy; energy dispersive spectroscopy; Fourie transform infrared spectroscopy and electrochemical impedance. Samples on disks and HAp and Nb2O5 powders were subjected to acute toxicity testing with Artemia salina Lesch. The results showed that the optimized composition with composite resin formed by 0.5g of nanohybrid resin with 0.02g Nb2O5 and 0.04g HAp did not interfere with the mechanical properties and appearance of the samples, but increased the resistance to corrosion, being a non-compound composite. favorable toxicant for use in the dental field.